If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -10 = -4 + 2x Reorder the terms: -10 + -1x = -4 + 2x Solving -10 + -1x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + -1x + -2x = -4 + 2x + -2x Combine like terms: -1x + -2x = -3x -10 + -3x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + -3x = -4 + 0 -10 + -3x = -4 Add '10' to each side of the equation. -10 + 10 + -3x = -4 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = -4 + 10 -3x = -4 + 10 Combine like terms: -4 + 10 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| -4(5t-3)+7t=4t-7 | | 4x-6=30-2x | | 4y-5y=10 | | 5(12x)=(x+7)+(6x+9)+(x+10) | | 21+29=35+22 | | 2x-5-x=-2 | | 0.02(y-8)+0.16y=0.08y-0.6 | | y=1100+25x | | -10(4m-2)=180 | | -3(6-3k)=2k+3 | | 1.6=logs | | 5v-v-1=19 | | 10x+2y+7z-5x+4z-4y= | | 2log(3x)+3=1 | | 4x-5y=-62x+3y=10 | | 6(L)-2(w)=126 | | -4s+2s=10 | | 17(2-3x)+5(5x-6)=4(3-8x)+10 | | 8k-(6k+k)=-(2k+6) | | y=20+6x | | 15p-13p-16= | | 5z-2= | | 4-3x+7=8-5x | | 7x+4=3+4x+22 | | 3X^2-35x=112+7x-4X^2 | | 1-m=6-6-6m | | 2(66)-6= | | 32.73=58.59(W-17.76) | | 4(x-6)=-2(x+3) | | 0-2x+1=0 | | 2w-6=126 | | z-4z=9z-6-z |